Micromechanical modelling of the longitudinal compressive and tensile failure of unidirectional composites: The effect of fibre misalignment introduced via a stochastic process - Varandas, Luis; Catalanotti, Giuseppe; Melro, Antonio; Tavares, Rodrigo; Falzon, Brian (Elsevier, 2020)
Initial fibre misalignment is recognised to be one of the precursors leading to longitudinal compressive failure in fibre-reinforced composites. Thus, to properly model their mechanical behaviour, an accurate spatial representation of the fibrous reinforcements must be assured. This work presents a three-dimensional micromechanical framework that is capable of analysing in detail the longitudinal tensile and compressive failure mechanisms which are inherent in unidirectional composites. This is achieved through the incorporation of initial fibre waviness via a combination of a stochastic process and an optimisation procedure. A robust micro-scale framework is developed by assigning, to both constituents and their interface, proper thermodynamically consistent damage models. Several microstructures having different degrees of misalignment are modelled and a clear trend is observed for the longitudinal compressive load case, i.e. by increasing initial fibre misalignment, the overall performance of the material decreases. In contrast, the models subjected to longitudinal tension exhibit a similar overall response, despite the misalignment. However, local mechanisms seem to change with the degree of friction and fibre misalignment, but these smaller-scale mechanisms do not play a decisive role on the overall longitudinal tensile performance of the material.